2021
DOI: 10.3389/fpubh.2021.610280
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Progression of COVID-19 Infection to Prioritize Medical Resource Allocation: A Novel Triage Model Based on Patient Characteristics and Symptoms at Presentation

Abstract: Background: The COVID-19 global pandemic has posed unprecedented challenges to health care systems all over the world. The speed of the viral spread results in a tsunami of patients, which begs for a reliable screening tool using readily available data to predict disease progression.Methods: Multicenter retrospective cohort study was performed to develop and validate a triage model. Patient demographic and non-laboratory clinical data were recorded. Using only the data from Zhongnan Hospital, step-wise multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the present study, we demonstrated two simple methods for predicting the development of illness among mild/moderate patients with COVID-19 that do not require blood sampling: DOAT and DOATS scores. Tu et al developed a model predicting the progression of COVID-19 consisting of nine items: sex, age, and the presence of a fever, hypertension, cardio-cerebrovascular disease, dyspnea, cough, and myalgia [ 14 ]. Their model also consisted of clinical characteristics only, with no laboratory data involved.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated two simple methods for predicting the development of illness among mild/moderate patients with COVID-19 that do not require blood sampling: DOAT and DOATS scores. Tu et al developed a model predicting the progression of COVID-19 consisting of nine items: sex, age, and the presence of a fever, hypertension, cardio-cerebrovascular disease, dyspnea, cough, and myalgia [ 14 ]. Their model also consisted of clinical characteristics only, with no laboratory data involved.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the eastern region, the number of general practitioners in the central and western regions is small. Meanwhile, although the number of general practitioners per 10,000 people in the eastern, central and western regions is on the rise, there are obvious regional differences between eastern, central, and western regions (Tu et al, 2021). The most widely used neural network model is the back propogation algorithm (BP) neural network.…”
Section: Introductionmentioning
confidence: 99%
“…per 10,000 people in the eastern, central and western regions is on the rise, there are obvious regional differences between eastern, central, and western regions (Tu et al, 2021). The most widely used neural network model is the back propogation algorithm (BP) neural network.…”
mentioning
confidence: 99%